Business and corporation engagement with higher education : models, theories, and best practices - Clevenger, Morgan R., 1969-; MacGregor, Cynthia J. (Cynthia Jane), 1962- (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book further explores the behavior aspects of corporate-higher education inter-organizational relationships by culminating various theories and models addressing the space where U.S. corporations and American higher education intersect. Examples are provided regarding the attraction, motivations, and maintenance needed for higher education to create win-win relationships with businesses. This work offers a new approach to the corporate citizenship literature by providing a broad, holistic review of frameworks to understand the range of motives and expectations of corporate engagement in the American society as evidenced by inter-organizational relationships with higher education. By providing an insight to better design and to manage inter-organizational relationships, this book will prove invaluable to both higher education practitioners and corporations alike.
Prelims -- At the intersect of business and higher education: historical, theoretical, and empirical perspectives on interorganizational relationships -- Long-term business agendas to contribute to society -- Corporate philanthropy -- Stakeholder management and corporate social responsibility (CSR) -- Corporate citizenship -- Inside corporations: how they think and behave -- How higher education thinks and behaves -- How higher education thinks and behaves -- Career development strategies serving businesses and corporations -- Modern expectations and implications: the new ecology, ethics, and future directions of interorganizational relationships -- Field of organizational theory concept map -- The additional enlightened companies -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Business and education -- United States; Academic-industrial collaboration -- United States; Education -- Higher; Higher & further education, tertiary education